An intervention to empower and engage the self-help groups for menstrual hygiene in Karnataka, India - RS, Reshmi; Gupta, Manoj Kumar; Kumar, Dhirendra; Visengrawala, Fehmida (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This paper was a part of ‘Multi-centric action research demonstration study’ with the aim to sensitize, mobilize and engage women regarding reproductive health through empowerment and engagement of the Self Help Groups (SHGs) women. The paper focuses on the effect of intervention on menstrual hygiene and health of women in Kolar district of Karnataka. Methods: As an intervention, a total of fifteen workshops, targeting 75 SHGs in each, were conducted using pre-developed IEC material in intervention taluk. A total of 400 households (200 from each intervention and control sites) of SHG women were interviewed for baseline and endline each Results: The intervention was found effective in the form of a significant improvement in the level of awareness regarding use of Napkins/sanitary pads and its disposal. Apart from this, the level of awareness regarding menstrual discharge abnormalities was also significantly improved. However, the intervention was insignificant in molding area specific misconceptions and practices during menstruation such as access to worship, entry into kitchen, mingle with people etc. Conclusions: The results of the present study clearly indicate the feasibility, efficacy and significant impact of health education interventions in improving the level of knowledge, attitude and practices of women regarding menstrual hygiene and point out that cost-effective strategy through information, education, and behavior change are needed in this regard.